Bethe Vectors for Composite Models with gl(2|1) and gl(1|2) Supersymmetry - Fuksa, J. (Symmetry, Integrability and Geometry: Methods and Applications, 2017)
Supersymmetric composite generalized quantum integrable models solvable by the algebraic Bethe ansatz are studied. Using a coproduct in the bialgebra of monodromy matrix elements and their action on Bethe vectors, formulas for Bethe vectors in the composite models with supersymmetry based on the super-Yangians Y[gl(2|1)] and Y[gl(1|2)] are derived.